Health Tourism System Development Using Entrepreneurial Management Approach in the COVID-19 Pandemic Era - Hossein Dargahi; Kambiz Talebi; Hamideh Reshadatjoo; Reza Dehghan (Gonabad University of Medical Sciences, 2021)
Background: Health tourism uses a set of services that promote the health and spirit of individuals through medical care. Entrepreneurship is a process of exploring and using value creation opportunities in the economic, cultural, social, and health sectors. The present study was done to investigate the development of Iran's health tourism system based on Stevenson's entrepreneurial management model and determine entrepreneurial opportunities during the COVID-19 outbreak. Methods: This descriptive quantitative research was conducted by the field study (survey) method, using a standardized and localized questionnaire from Stevenson's entrepreneurial management model to examine the views of health tourism specialists as the statistical population of the study. Using the snowball sampling method, 357 health tourism specialists, university professors, and health system managers participated in this study from 2018 to 2020. The collected data were recorded in PLS Smart software and their analysis was performed using descriptive and inferential statistics. Results: The findings indicated that all six components of Stevenson's entrepreneurial management had a significant effect on the health tourism industry's development. Strategic orientation and commitment to opportunities (path coefficient: 0.83) had the maximum effect, while the reward philosophy (path coefficient: 0.41) had the minimum effect on developing the health tourism industry. Conclusion: The average status of Stevenson's entrepreneurial management dimensions in the health tourism industry was evaluated. Some of these factors (strategic orientation and commitment to opportunities) were obviously more favorable than others. Proper entrepreneurial strategies and the use of situations can provide good opportunities in health tourism.